2022
DOI: 10.1038/s41467-022-30507-0
|View full text |Cite
|
Sign up to set email alerts
|

Global diversity dynamics in the fossil record are regionally heterogeneous

Abstract: Global diversity patterns in the fossil record comprise a mosaic of regional trends, underpinned by spatially non-random drivers and distorted by variation in sampling intensity through time and across space. Sampling-corrected diversity estimates from spatially-standardised fossil datasets retain their regional biogeographic nuances and avoid these biases, yet diversity-through-time arises from the interplay of origination and extinction, the processes that shape macroevolutionary history. Here we present a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 80 publications
(103 reference statements)
4
43
0
2
Order By: Relevance
“…Origination rate may be also affected by diversity-dependent species population abundances if species with smaller populations have lower probability to speciate (20,21). In addition, if origination rates are linked to niche differentiation (24), then they may decrease with increasing diversity because of niche filling. These two possibilitiesdiversity dependence mediated by changing species abundances and by changing niche availability-are not exclusive, as niche availability and niche filling almost certainly affect abundances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Origination rate may be also affected by diversity-dependent species population abundances if species with smaller populations have lower probability to speciate (20,21). In addition, if origination rates are linked to niche differentiation (24), then they may decrease with increasing diversity because of niche filling. These two possibilitiesdiversity dependence mediated by changing species abundances and by changing niche availability-are not exclusive, as niche availability and niche filling almost certainly affect abundances.…”
Section: Discussionmentioning
confidence: 99%
“…Process-based approaches also have potential to control for various statistical artifacts that might, even if slightly, distort the presented information flow analyses [such as the regression to the mean sensu ( 22 ); see Materials and Methods for detailed discussion). To explore biodiversity dynamics in paleontological series in a mechanistic and parametric manner, we need further development of quantitative theories of biodiversity dynamics applicable to large spatial and temporal scales ( 20 , 23 ), coupled with analytical tools able to deal with noise, various biases, and artifacts that are inherently present in paleontological time series ( 3 , 10 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 , S2 , S3 b), which is why associated peaks or apparently constant rates should be interpreted with caution. Future investigations should attempt to incorporate spatial biases in the analyses 68 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the effect of each extinction event on insect genera, we found that the LPME had the strongest impact with the demise of 82.6% of genera, followed by the L/C impact with 74.8%, while the effect of the R/W extinction was less pronounced with the extinction of 64.5% of insect genera (Supplementary Table 1). Importantly, it is the first time, to our knowledge, that extinction peaks are recorded at the R/W and L/C boundaries for insects, while a huge loss of diversity is known for vertebrate clades at this time 41,42 . Conversely, the GEE and CPE are not recorded, and the R/ W or L/C extinctions cannot be mistaken for these events because they occurred long before them.…”
Section: Unexpected and Heterogenous Extinctions During The Permian A...mentioning
confidence: 88%